Association of interleukin-17A gene polymorphisms and susceptibility to systemic lupus erythematosus in Egyptian children and adolescents: a multi-centre study. (June 2020) - Elkoumi, Mohamed A; Allah, Mayy AN; Mohamed, Faisal Y; Boraey, Naglaa F; Abdellatif, Sawsan H; Shehab, Mohamed MM; Sherif, Ahmed H; Akeel, Nagwa E; Saleh, Rabab M; Elshreif, Anas M; Abdelrahman, Hind M; Soliman, Attia A; et al.
Background: Recently, the interleukin-17A ( IL-17A ) gene has emerged as a potential candidate gene for autoimmune disorders, including systemic lupus erythematosus (SLE). Objectives: This study aimed to investigate whether IL-17A polymorphisms at rs2275913 G/A, rs8193036 C/T and rs3748067 C/T could be susceptibility markers for juvenile-onset SLE (JSLE) and lupus nephritis (LN) in Egyptian children and adolescents. Methods: In this multi-centre study, we genotyped 320 patients diagnosed with JSLE and 320 matched control children for three IL-17A polymorphisms at rs2275913 G/A, rs8193036 C/T and rs3748067 C/T using TaqMan probe-based real-time polymerase chain reaction. Meanwhile, IL-17A serum levels were assessed using ELISA. Results: The IL-17 rs2275913 A/A genotype and A allele were more represented in JSLE patients compared to the control group (21% vs. 7%, odds ratio (OR) = 3.8, 95% confidence interval (CI) 1.78–5.5, p  = 0.001, p Bonf = 0.003 for the A/A genotype; 37% vs. 29%, OR = 1.4, 95% CI 1.11–1.8, p  = 0.003, p Bonf = 0.009 for the A allele. No significant difference was found for IL-17 rs8193036 and rs3748067 single nucleotide polymorphisms (SNPs) in genotype distribution or allele frequencies ( p >0.05). Patients carrying the IL-17 rs2275913 A/A genotype and A allele were more likely to develop LN (OR = 5.64, 95% CI 2.39–13.77, p Bonf = 0.001 for the A/A genotype; OR = 2.73, 95% CI 1.84–4.07, p Bonf = 0.02 for the A allele). Conclusion: The IL-17 rs2275913 A allele and A/A genotype were associated with high IL-17 serum levels and may contribute to susceptibility to JSLE and the development of LN in Egyptian children and adolescents. However, no significant association was evident between the studied IL-17A SNPs and other clinical phenotypes, disease activity scores or laboratory profile of JSLE.